2013
DOI: 10.4236/ojemd.2013.32022
|View full text |Cite
|
Sign up to set email alerts
|

Design of the Saitama Cardiometabolic Disease and Organ Impairment Study (SCDOIS): A Multidisciplinary Observational Epidemiological Study

Abstract: Background:In the past few decades, the incidence of cardiometabolic diseases and disorders of the liver, kidney, pancreas, heart, and lung, have been increasing in Western and Asian countries, including Japan. Numerous factors, including abnormal body weight (obesity, overweight, or underweight), infrequent exercise, and other unfavorable lifestyle factors (e.g., smoking and heavy alcohol drinking) have been proposed as risk factors for the development and the progression of diseases, such as type 2 diabetes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 96 publications
0
24
0
Order By: Relevance
“…This preliminary cross-sectional study was part of an observational study that was performed to examine the relationships between lifestyle-related diseases and cardiometabolic risk factors (Muneyuki et al 2013). The current study involved 2 institutions in Kanagawa and Saitama, Japan: Kanagawa University of Human Services and the Saitama Health Promotion Corporation, a public interest corporation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This preliminary cross-sectional study was part of an observational study that was performed to examine the relationships between lifestyle-related diseases and cardiometabolic risk factors (Muneyuki et al 2013). The current study involved 2 institutions in Kanagawa and Saitama, Japan: Kanagawa University of Human Services and the Saitama Health Promotion Corporation, a public interest corporation.…”
Section: Methodsmentioning
confidence: 99%
“…BMI was calculated as body weight (kg) divided by height squared (m 2 ). Subjects were divided into six BMI categories (≤18.9, 19.0–20.9, 21.0–22.9, 23.0–24.9, 25.0–26.9, and ≥ 27.0 kg/m 2 ), as previously reported (Muneyuki et al 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of this study is described in more detail elsewhere [17]. This retrospective study consists of data recorded during annual medical checkups of asymptomatic individuals living or working in Saitama Prefecture, a suburb of Tokyo, Japan.…”
Section: Methodsmentioning
confidence: 99%
“…clinical significance (1,7,8). However, several studies have suggested that TrP is highly likely to progress to microalbuminuria (3,7,9).…”
mentioning
confidence: 99%